Pregnancy-Induced Hypertension and Gestational Diabetes Impact on Fetomaternal Outcomes in COVID-19-Positive Women Hospitalized for Delivery (Journal of Fatima Jinnah Medical University, 2024)
Background: Studies evaluating the impact of pregnancy-related disorders among COVID-19-positive women on fetomaternal outcomes remained scarce. Therefore, we assessed the impact of pregnancy-induced hypertension (PIH) and gestational diabetes mellitus (GDM) on fetomaternal outcomes in COVID-19-positive women hospitalized for delivery.Patients and methods: A review of medical records of 37 COVID-19-positive pregnant women hospitalized at Sir Ganga Ram Hospital Lahore from April to June 2020 was performed. Data retrieved included demographics, comorbid illnesses, and maternal and fetal outcomes. Using SPSS v.26, a Chi-square test was done to assess the impact of comorbid illnesses on fetomaternal outcomes.Results: The mean age of the cases was 25.8 ± 4.6 years, the gestational age was 37.5 ± 1.2 weeks, and the frequency of primigravida was 24.3%. PIH (n = 08, 21.6%) was the most frequent comorbid illness followed by GDM (n = 05, 13.5%). Women with comorbid illness showed statistically significant differences for cesarean delivery (64.3% vs. 35.7%, p-value = 0.022), duration of hospital stay (8.2±3.8 vs. 5.6±1.6 days, p-value = 0.009), low birth weight (85.7% vs. 14.3%, p-value = 0.007), NNU admission (60.0% vs. 40.0%, p-value = 0.009), and marked differences for both maternal and neonatal mortality (100% vs. 0.0%, p-value = 0.078) as compared to women without any comorbid illness, respectively.Conclusions: Comorbidities including PIH and GDM among COVID-19-positive women hospitalized for delivery, had a higher incidence of adverse fetomaternal outcomes and longer hospital stay. These findings suggest that women with comorbid illness require personalized treatment to prevent or decrease poor pregnancy outcomes.
Keywords: COVID-19; Comorbidities; Gestational diabetes; Pregnancy induced hypertension; Fetomaternal outcome